Ambient Computing to Support the Association ofContextual Cues with Medication Taking - Rodriguez, M. D.; Zárate, E.; Stawarz, K.; García-Vázquez, J. P.; Ibarra, E. J. (Revista Mexicana de Ingenieria Biomedica, 2015)
The most common reason for non-adherence to medication among older adults is forgetfulness. Contextual cues, such as daily routines, serve as implicit situational information that increases the retrieval process of the intended action. The main contribution is an overview of the process and the technical details of Ambient Computing displays we developed to help seniors use contextual cues to remember actions associated with medication intake (i.e. remember to take medications or remember having taken them earlier). Through a qualitative study, we obtained evidence about the potential of our technological approach to make seniors more responsible and independent for taking medications.